2007
DOI: 10.4103/0255-0857.34767
|View full text |Cite
|
Sign up to set email alerts
|

Melioidosis: An under-diagnosed entity in western coastal India: A clinico-microbiological analysis

Abstract: Clinico-microbiological analysis of a series of 25 patients with culture proven melioidosis was done. All patients came from the coastal regions of Kerala and Karnataka and presented between June 2005 to July 2006. They were analysed with respect to clinical presentation, occupation, epidemiology and microbiological features. No single presenting clinical feature was found to be typical of melioidosis. The disease was found to mimic a variety of conditions, including tuberculosis and malignancy. Burkholderia p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 7 publications
4
39
0
Order By: Relevance
“…8 Although healthy people may get melioidosis, the major risk factors include diabetes (present in 23-60% of patients), heavy alcohol use (in 12-39%), chronic pulmonary disease (in 12-27%), chronic renal disease (in 10-27%), thalassemia (in 7%), glucocorticoid therapy (in <5%), and cancer (in <5%). 9 In an Indian series by Vidyalakshmi et al 10 predisposing factors were present in all the patients, of which the commonest was diabetes mellitus, which was present in 76% of the patients. The other predisposing conditions in this series included renal disease, steroid therapy and malnutrition, alcohol abuse, and chronic lung disease.…”
Section: Discussionmentioning
confidence: 95%
“…8 Although healthy people may get melioidosis, the major risk factors include diabetes (present in 23-60% of patients), heavy alcohol use (in 12-39%), chronic pulmonary disease (in 12-27%), chronic renal disease (in 10-27%), thalassemia (in 7%), glucocorticoid therapy (in <5%), and cancer (in <5%). 9 In an Indian series by Vidyalakshmi et al 10 predisposing factors were present in all the patients, of which the commonest was diabetes mellitus, which was present in 76% of the patients. The other predisposing conditions in this series included renal disease, steroid therapy and malnutrition, alcohol abuse, and chronic lung disease.…”
Section: Discussionmentioning
confidence: 95%
“…of contaminated dust and direct entry of the organism into blood stream via very minor wounds or skin abrasions [4]. Other modes of transmission are aspiration and ingestion of contaminated water.…”
Section: Resultsmentioning
confidence: 99%
“…In our patient diabetes was an incidental finding during the course of investigation. Vidyalaxmi et al [4] found a correlation of 76% of diabetes with Melioidosis. Two commonest modes of transmission are inhalation BD.…”
Section: Discussionmentioning
confidence: 98%
“…4 One case of cellulitis of neck with septicemia was reported. 3 Fever with multiple abscesses with underlying osteomyelitis is rare.…”
Section: Discussionmentioning
confidence: 99%
“…2 Sporadic cases of melioidosis from various parts of South India 3 and Western costal India have been reported, but remained underdiagnosed due to lack of awareness. 4 …”
Section: Introductionmentioning
confidence: 99%